Pelagomanes kozoi, n. comb. - Trubovitz, Sarah; Renaudie, Johan; Lazarus, David; Noble, Paula (Zenodo, 2022)
Pelagomanes kozoi (Renaudie and Lazarus, 2013a) n. comb. Plate 39, Figs. 1–6. Lithomelissa setosa Jørgensen, Takahashi, 1987, pl. 5, fig. E. ? Ceratocyrtis? sp. aff. C. stigi (Bjørklund), Sugiyama and Furutani, 1992, pl. 13, fig. 13. Lithomelissa sp. D, Itaki et al., 2008a, pl. 1, fig. 6. Lithomelissa sp. D, Itaki et al., 2009, pl. 17, figs. 15–23. Lithomelissa ? kozoi n. sp., Renaudie and Lazarus, 2013a, pl. 5, figs. 10a–11, 13a–b; pl. 8, fig. 5. Lithomelissa ? kozoi Renaudie and Lazarus, Trubovitz et al., 2020, supplementary data 7. Remarks. In our plates we provide images of Pelagomanes kozoi from both the EEP and the SO, where it was originally described. Figures 1–4B are of specimens observed during this study in the EEP. Specimen 6 is the holotype and specimen 5 is another specimen that was figured by Renaudie and Lazarus 2013a in their description. Both specimens are from the Late Pliocene Southern Ocean. Among the SO and EEP specimens there are some variations in overall size and shoulder development. This species differs from Pelagomanes ibburi n. sp. (Pl. 41, Figs. 1A – 6B) in that it has multiple teeth of approximately equal strength, rather than three feet stronger than the rest. It differs from P. stigi (Bjørklund) (Pl. 39, Figs. 7–9) in having relatively smaller pores throughout the cephalis and thorax, more distinct shoulders and ribs, and usually a less prominent apical horn. P. kozoi is smaller than P. thaumasia (Pl. 39, Figs. 10A –11), has more shoulder development, is usually not as heavily silicified, and has more prominent teeth at the base of the thorax. This species differs from P. cantharoides (Pl. 40, Figs. 1–3, 7–8, 10, 14) in that the apical horn is not as strong, and it does not have any additional branching on the dorsal side. P. kozoi is smaller than both P. cantharoides and P. morawanensis (Pl. 40, Figs. 4A – 6, 9, 11–12). Based on our understanding of P. tekopua (O’Connor 1997) (pl. 40, Fig. 13), P. kozoi differs in having a relatively smaller cephalis:thorax ratio and lacks ...